Modular parsers - Dobson, Simon (Trinity College Dublin, Department of Computer Science, 1998)
Traditional parser generators are designed to produce highly optimised parsers for grammars known in their entirety ahead of time. There are some circumstances where it is desirable to construct a parser from grammar fragments, for which the flexibility of combination is more important than the speed of the final parser. We describe a system of parser components, generating parsers for grammar fragments and which may be combined using a small set of parser combinators to produce a final parser.
Keywords: Computer Science